VARIABLE SELECTION IN STRUCTURAL EQUATION MODELLING OF FACTORS INFLUENCING T HE SUCCESS OF THE WEARABLE DEVICE INDUSTRY IN WENZHOU, CHINA - Wang, Chengsi; Tonglim, Tongtang; Thurapaeng, Chertchai (Asia Pacific Journal of Religions and Cultures, 2024)
The research on “Variable Selection in Structural Equation Modeling of Factors Influencing the Success of the Wearable Device Industry in Wenzhou, China” aimed to 1) study the variables (factors) of the wearable device industry in Wenzhou, China, and 2) identify and select the most significant factors influencing the success of the wearable device industry in Wenzhou, China. The research methodology was variable selection methods in Structural Equation Modeling (SEM), including the focus group and grounded theory. The study results found that the rapid evolution of China's wearable technology industry, driven by advancements, manufacturing expertise, and consumer demand, has made it a global key player. Variables selected from the study that affect the success of the wearable device industry are categorized into 3 major variables and their sub-variables are (1) technological; sensor accuracy, battery life, connectivity, and user interface design, (2) market-related; pricing strategy, brand reputation, distribution channels, and (3) socio-cultural; cultural preferences, social norms, social attitudes. Since the socio-cultural factor reflects significantly on consumer behaviors through technology. Key indicators of success as the dependent factor include market preference, consumer satisfaction, and financial viability, emphasizing the importance of innovation and culturally appropriate designs. The variable selection method used in this study is helpful and useful for academic purposes when proceeding with structural equation modeling research.